Self-consistent approach for magnetic ordering and excited site occupation processes in a two-level system - Korynevskii, M.A.; Solovyan, V.B. (Condensed Matter Physics, 2015)
Ferromagnetic ordering in a two-level partially excited system is studied in details. Magnitudes of magnetization (magnetic order parameter) and lattice ordering (excited level occupation number) are calculated self-consistently. The influence of an external magnetic field and excited level gap on the ferromagnetic phase transition is discussed. Детально вивчено процес феромагнiтного впорядкування у дворiвневiй частково збудженiй системi.
Величина намагнiченостi (магнiтний параметр впорядкування) та граткове впорядкування (заповнення
збуджених рiвнiв) розрахованi самоузгоджено. Обговорено вплив зовнiшнього магнiтного поля i ширини енергетичної щiлини мiж основним i збудженим рiвнями на феромагнiтний фазовий перехiд.